2022
DOI: 10.1155/2022/2378253
|View full text |Cite
|
Sign up to set email alerts
|

CKAP2L Promotes Esophageal Squamous Cell Carcinoma Progression and Drug-Resistance by Modulating Cell Cycle

Abstract: Esophageal squamous cell carcinoma (ESCC) is one of the most common types of cancer and the leading cause of cancer-related mortality worldwide, especially in Asia. In this study, the gene CKAP2L was selected by GEO, TCGA, and GTEx database analysis. The high expression of CKAP2L is related to the occurrence and development of ESCC. In addition, CKAP2L knockdown can inhibit the growth and migration of ESCC cells, while CKAP2L overexpression has the opposite effect. Furthermore, in vivo experiments indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Flow cytometry results showed that knockdown of CKAP2L resulted in cell cycle G2/M arrest. Similar to previous studies 5 7 , we suggested that CKAP2L may contribute to tumor progression in KIRC by influencing the biological behavior of cancer cells through the cell cycle too. However, we only validated the effect of CKAP2L in KIRC and further studies are needed to assess the role of CKAP2L in the other tumors.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Flow cytometry results showed that knockdown of CKAP2L resulted in cell cycle G2/M arrest. Similar to previous studies 5 7 , we suggested that CKAP2L may contribute to tumor progression in KIRC by influencing the biological behavior of cancer cells through the cell cycle too. However, we only validated the effect of CKAP2L in KIRC and further studies are needed to assess the role of CKAP2L in the other tumors.…”
Section: Discussionsupporting
confidence: 90%
“…CKAP2L is a mitotic spindle protein that has been previously shown to be overexpressed in some tumors and to be associated with tumor progression and patient prognosis. In prostate cancer, esophageal squamous cell carcinoma and glioblastoma, CKAP2L has been shown to affect the biological behavior of cancer cells by regulating the cell cycle 5 7 . A breast cancer study has shown that CKAP2L activates the AKT/mTOR signaling pathway and thus promotes breast cancer development 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation